Taklik Talak as a Safeguard for Women's Rights within the Family: A Hermeneutic Analysis of Legal Perspectives - Jalil, Abdul Jalil; Zahrotul, Zahrotul Habibah; Kudrat, Kudrat Abdillah (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2025)
Problem statement: cases of violence against women within the family are becoming increasingly serious and must be addressed to ensure that women can secure their rights. The social construct of pre-Islamic Arab ignorance, which remains prevalent today, is a patriarchal system that positions women as second-class citizens, often violating the principle of ‘mutuality’ in family relationships. Legally, the state has established a framework for women's rights as legal subjects; however, this framework does not yet adequately address internal rights within family relationships. The presence of divorce by conditional stipulation (taklik talak), as one of the forms of legal redress currently being pursued, continues to evoke various perceptions and interpretations. Objective: therefore, this study aims to analyse the substance of the taklik talak text as a means of protection for women's rights within the family from a legal hermeneutic perspective. Methods: this research is classified as normative legal research with an analytical approach, examining the taklik talak text in the Marriage Book. Data collection techniques were conducted through a literature review employing a systematic descriptive analysis method from a legal hermeneutic perspective. Results: the findings of this study indicate that the substance of taklik talak historically aims to provide protection for women. Conclusion: based on the analysis from the legal hermeneutics perspective, the taklik talak text represents a commitment by the husband not to neglect his obligation to provide maintenance, not to abandon his wife, and not to cause her physical harm; thus, the agreement functions as a form of guarantee of women's rights for the preservation of marriage.